REPRESENTASI DAN NILAI KEARIFAN EKOLOGI PUISI “HUJAN BULAN JUNI” KARYA SAPARDI DJOKO DAMONO ( EKOKRITIK GREG GARRARD) - Setiaji, Aria Bayu (LP2M IAIN Ambon, 2020)
Abstract Poetry is a representation of the author in expressing feelings, experiences and insights. Poetry is written or created by writers not to be read alone, but there are ideas, ideas, experiences, messages and criticisms to be conveyed to the reader. This research specifically aims to obtain a literary ecological criticism of Sapardi Djoko Damono's poem Hujan Bulan Juni which includes (1) How is nature represented in poetry? (2) What role can the physical setting (environment) play in the plot of a poem? (3) What are the values expressed in a poem? The theory used to analyze the poem is Greg Garrard's echocritic. Data analysis was carried out descriptively. The results of the analysis in the Hujuju Bulan Juni poem show that the author / writer dominates the use of diction with representations of nature, earth and plants. The author tries to explore ways on how to describe the relationship between humans, the environment, nature and plants so as to foster ecological values of human concern for protecting and preserving the environment, nature and plants. Keywords: Poetry. Ecocritic, Literature Abstrak Puisi merupakan suatu representasi penulis dalam mengungkapkan perasaan, pengalaman maupun wawasan. Puisi ditulis atau dicipkaan oleh sastrawan bukan untuk dibaca sendiri, melainkan ada ide, gagasan, pengalaman, amanat dan kritikan yang ingin disampaikan kepada pembaca. Penelitian ini secara khusus bertujuan untuk memperoleh kritik ekologi sastra puisi Hujan Bulan Juni karya Sapardi Djoko Damono yang meliputi (1) Bagaimana alam direpresentasikan dalam puisi? (2) Peranan apa yang dapat dimainkan oleh latar fisik (lingkungan) dalam alur sebuah puisi? (3) Apakah nilai-nilai yang diungkapkan dalam sebuah puisi Teori yang digunakan untuk menganalisis puisi tersebut adalah ekokritik Greg Garrard. Analisis data dilakukan secara deskriptif. Hasil analisi Pada puisi Hujuaan Bulan Juni menunjukkan bahwa pengarang/penulis mendominasi pengunaan diksi dengan representasi alam, bumi dan tumbuh-tumbuhan. Penulis mencoba mengeksplorasi cara-cara mengenai bagaimana menggambarkan hubungan antara manusia ,lingkungan,,alam dan tumbuh-tumbuhan sehinga menumbuhkan nilai-nilai ekologi kepedulian manusia untuk menjaga dan melestarika lingkungan, alam dan tumbuh-tumbuhan. Kata Kunci : Puisi. Ekokritik, Sastra